The Growing Chinese Interests in the Middle East: Prospects of Saudi-Iran Rapprochement - Mashwani, Hassan Farooq; Waheed, Abdul; Shahzad, Samiya (Pakistan Languages and Humanities Review, 2024)
The paper aims to study the Chinese growing interests in the Middle east and its implications for Saudi-Iran rapprochement. For the exceptional rise of China and its energy requirements the Middle East stands one of the most attractive destinations for its foreign policy. The recently held Sino-Arab Summit reflects Beijing's growing interests and influence in the region. Major focus of the Arab-Chinese ties lies in economic development and peaceful resolution of the regional disputes. Beijing mediated the restoration of Riyadh-Tehran diplomatic ties between the two ideological rivals, representing opposing Islamic sects - Sunni and Shia Muslims. The data has been mainly collected through secondary sources with exploratory research design. The Saudi-Iran conflictual ties can hinder Chinese trade and investment in the Middle East therefore, it has keenly assisted the Saudi-Iran rapprochement. Iran and Saudia need to capitalize Chinese growing economic and political interests in the Middle East that will be helpful for the regional and global peace and stability.